The Use of Question Answer Relationship (QAR) Strategy to Improve the Eighth Grade Students’ Reading Comprehension Achievement at Junior High School - Febriana Silvia Sukma Hunaidar; Sudarsono Sudarsono; Zakiyah Tasnim (EFL Education Journal, 2021)
This research was aimed at improving the eighth-grade students’ reading achievement and their participation during teaching-learning proses using the QAR Strategy. This research applied CAR design with grade eight students of secondary school as the research participants. The data were analyzed using descriptive statistic to know how students’ reading comprehension achievement and the students’ participation could get improvedafter being taught using QAR strategy. This research was conducted in 1 cycle. The result of this research shows that the use of the QAR Strategy could improve the students’ reading comprehension achievement and the students’ participation during the teaching and learning process.